Hydrogeology And Geochemistry of an Inactive Hazardous Chemical and Low-Level Radioactive Waste Landfill, Manhattan, Kansas - Nold, Eric (Kansas State University, 1995)
The KSU inactive hazardous chemical and low-level radioactive-waste landfill located on the North Agronomy Research farm was used for waste disposal from the early 1960s until 1988. The landfill is situated in sediments deposited during the Pleistocene glaciation. The Quaternary age sediments are approximately 65 ft thick, consist of a heterogeneous mixture of clayey silt and silty sand, and overlie Permian bedrock. Drainage across the landfill is east toward a small ephemeral stream which drains to the northeast and empties onto the flood plain of the Big Blue River. Groundwater flow generally mimics surface drainage, with an average slope of 0.03 eastward, but the water table directly east of the landfill has a low ground-water divide that separates flow to the northeast and southeast. Nine monitoring wells were installed at the landfill at a 20 ft depth, screened in the lower 10 ft for water-table observation. One well was installed at 63 ft, screened in the lower 5 ft, to monitor the sand and gravel aquifer overlying Permian bedrock; and one well was installed 30 ft deep and screened in the lower 5 ft to help in determining the depth of ground-water contamination. The 63 ft and 30 ft well were screened below the water table and have hydraulic heads higher than the adjacent wells monitoring the water table, indicating an upward component of flow in the vicinity of the landfill. Pump tests performed on water-table monitoring wells revealed low hydraulic conductivities averaging 0.0014 in/min. Chemical analysis of water samples reveals that ground-water flowing southeast from the landfill is consistently higher in total dissolved solids, is harder, and is more likely to precipitate calcium carbonate than water flowing to the northeast. Ground- water flowing southeast is also consistently higher in organic contaminants. Benzene is the organic compound detected with the highest concentration at the site, reaching a maximum of 4900 ppb. The concentration of benzene seems to be associated with water-level elevations, with concentrations rising during water levels above an altitude of 1,072 ft, and dropping as the water level falls below 1,072 ft. The concentration of benzene has a logarithmic decrease toward the eastern most monitoring wells at the landfill, with the highest concentration in those wells detected below 3.0 ppb. No organic contaminants were observed to have migrated beyond the landfill boundary at a concentration above 3.0 ppb and because of the low hydraulic conductivity, upward flow, and high clay content, it is unlikely any will in the near future.
Keywords: Low-Level Radioactive Waste Landfill